The last days of night [large type] - Moore, Graham, 1981- (Center Point Large Print, 2016)
"In this historical thriller about the nature of genius, the cost of ambition, and the battle to electrify America, a young lawyer fresh out of Columbia Law School takes a case that seems impossible to win. His client, George Westinghouse, has been sued by Thomas Edison over who invented the light bulb"--